PENGGUNAAN INTERNET DAN KONDISI EMOSIONAL SISWA DI SMP NEGERI 9 PEKANBARU - Tiurma Aritonang; Rosmawati Rosmawati; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Use of the Internet and Emotional Conditions to Students in SMP Negeri 9 Pekanbaru. This study covers about the increasingly rapid use of the Internet. The high number of internet users is dominated by teenagers. And now students can not be separated from the internet. The existence of a visible stimulus in the internet this makes students generate a response. Before the response arises, the brain first processes the stimulus. One form of response that arises is the emotion. So, the purpose of this research is to know the general picture of internet usage of students in general and to know the picture of emotional condition using internet student in SMP Negeri 9 Pekanbaru. The method used is descriptive method. The data collection tool used is a questionnaire. The population in this study is class IX. Class IX consists of 9 classes. The collection of random sampling is the class, which is 50% of the total population. So, there are 4 classes that are so sample in this research. The results of research that has been done, then the picture of the use of the internet in general in SMP Negeri 9 Pekanbaru is in the category of being. And in line with the use of this internet, researchers also see a picture of the emotional state of students who use the internet is in the category of being. The conclusion obtained is the dominant use of internet in the medium category for the three aspects of information interests (information utility), fun activities (fun activities) and email. Students who use the internet have happy emotions, and are sad at high categories, fearful and angry in the medium category. In happy emotions experienced are happy, happy, and carefree. In the sad emotions experienced are grief, longing and sadness. In the emotions of fear experienced are fear, worry, anxiety and restlessness. And the angry emotions experienced are anger, growl and disgust.Keyword: Emotional Condition, Internet Usage